Systematic Literature Review: Peningkatan Kemampuan Literasi Numerasi Siswa SD Melalui Pendekatan Media Pembelajaran Berbasis Game - Roslita Anggraeni; Daffa Aulia Rahmadanti; Ratna Dwi Aryanti; Azizah Syifa Az Zahra; Fina Fakhriyah; Nur Fajrie (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to improve the numeracy literacy skills of elementary school students through a game-based learning media approach. The background is the low numeracy literacy skills of Indonesian students compared to other countries, as shown by the results of the PISA and TIMSS tests. Many elementary school students still have difficulties in reading, understanding, and applying numerical information and basic mathematics in everyday life. The research method used is systematic literature review by analyzing journals related to improving numeracy literacy skills through game-based learning media. The results of the review show that the use of game-based learning media can effectively improve the numeracy literacy skills of elementary school students. Game-based learning is able to make math learning more interesting, interactive, and increase student motivation. The implication of this research is the importance of developing and implementing game-based learning media to improve students' numeracy literacy skills in elementary schools.